DEAP1 encodes a fasciclin‐like arabinogalactan protein required for male fertility in rice. Issue 7 (2nd June 2022) - Zhou, Dan; Zou, Ting; Zhang, Kaixuan; Xiong, Pingping; Zhou, Fuxing; Chen, Hao; Li, Gongwen; Zheng, Kaiyou; Han, Yuhao; Peng, Kun; Zhang, Xu; Yang, Shangyu; et al.
ABSTRACT: Arabinogalactan proteins (AGPs) are widely distributed in plant cells. Fasciclin‐like AGPs (FLAs) belong to a subclass of AGPs that play important roles in plant growth and development. However, little is known about the biological functions of rice FLA. Herein, we report the identification of a male‐sterile mutant of DEFECTIVE EXINE AND APERTURE PATTERNING1 ( DEAP1 ) in rice. The deap1 mutant anthers produced aberrant pollen grains with defective exine formation and a flattened aperture annulus and exhibited slightly delayed tapetum degradation. DEAP1 encodes a plasma membrane‐associated member of group III plant FLAs and is specifically and temporally expressed in reproductive cells and the tapetum layer during male development. Gene expression studies revealed reduced transcript accumulation of genes related to exine formation, aperture patterning, and tapetum development in deap1 mutants. Moreover, DEAP1 may interact with two rice D6 PROTEIN KINASE‐LIKE3s (OsD6PKL3s), homologs of a known Arabidopsis aperture protein, to affect rice pollen aperture development. Our findings suggested that DEAP1 is involved in male reproductive development and may affect exine formation and aperture patterning, thereby providing new insights into the molecular functions of plant FLAs in male fertility. Abstract : DEFECTIVE EXINE AND APERTURE PATTERNING1 ( DEAP1 ) encodes a plasma membrane‐associated fasciclin‐like arabinogalactan protein that preferentially accumulates in reproductive cells and the tapetum layer. DEAP1 plays a crucial role in exine formation and aperture patterning during rice pollen development, possibly by interacting with rice D6 PROTEIN KINASE‐LIKE3 proteins.